Male ductal carcinoma in situ (DCIS): Treatment strategies in this rare entity - Aznan M.S.; Affirul C.A.; Rohaizak M.; Razrim Rahim (Societa Editrice Universo, 2024)
Ductal carcinoma in situ (DCIS) in females is a recognized premalignant disease. However, its occurrence in males is rare. Articles describing this disease are scarce with documented occurrence is less than 7% worldwide. We report a case of 52 year-old gentleman presented with 6 months history of left breast lump. It was painless with no nipple discharge. Despite an inconclusive biopsy, lumpectomy was performed in view of the suspicion of malignant disease. Histopathology confirms DCIS. He underwent mastectomy and sentinel lymph nodes. Most treatment strategies are based on evidence on female breast malignancy and modifications are needed due to the different pathological pathway in male. Societ Editrice Universo (SEU).